2013
DOI: 10.1021/mp300378y
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Thermal Unfolding and Aggregation of Human IgG1 Fc Fragment by Hofmeister Anions

Abstract: The thermal unfolding and subsequent aggregation of the unglycosylated Fc fragment of a human IgG1 antibody (Fc) were studied in the salt solutions of Na(2)SO(4), KF, KCl and KSCN at pH 4.8 and 7.2 below and at its pI of 7.2, respectively, using differential scanning calorimetry (DSC), far ultraviolet circular dichroism (far-UV CD), size exclusion chromatography (SE-HPLC) and light scattering. First, our experimental results demonstrated that the thermal unfolding of the C(H)2 domain of the Fc was sufficient t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 29 publications
6
32
0
Order By: Relevance
“…46,47 The difference in the stability due to the presence of anions could be interpreted in terms of change in the hydration level and ion interaction. 48 Based on the previous and this research, the free energy diagram between native state, N, and denatured state, D, of MAb-T in AB5 and CB5 was depicted in Figure 5b. When MAb-T exists in the electrolyte solution, the Gibbs free energy is required to hydrate while a removal of hydration water by ion interaction decreased the free energy state.…”
Section: Molecular Basis For the Higher Conformational Stability Of Mmentioning
confidence: 89%
“…46,47 The difference in the stability due to the presence of anions could be interpreted in terms of change in the hydration level and ion interaction. 48 Based on the previous and this research, the free energy diagram between native state, N, and denatured state, D, of MAb-T in AB5 and CB5 was depicted in Figure 5b. When MAb-T exists in the electrolyte solution, the Gibbs free energy is required to hydrate while a removal of hydration water by ion interaction decreased the free energy state.…”
Section: Molecular Basis For the Higher Conformational Stability Of Mmentioning
confidence: 89%
“…However, such effects are usually observed at much higher salt concentrations. 44 An alternative hypothesis is that preferential accumulation of citrate ions (compared to acetate) results in reduced repulsions between proteins, and this increases aggregation rates at a given temperature. Increased aggregation rates will also shift T m app values to lower temperatures.…”
Section: Temperature-dependent Aggregation Ratesmentioning
confidence: 99%
“…Those questions notwithstanding, the results in Figure 3, Figure 6 and Supporting Information highlight that statistically precise E a values are needed to be able to better assess different contributions to aggregation rates occur at ion concentrations much lower than those typically reported for so-called Hofmeister effects. 44,52 Future work will focus on determining whether this behavior holds for a wider range of proteins and salts in the Hofmeister series at low salt concentrations.…”
Section: Temperature-dependent Aggregation Ratesmentioning
confidence: 99%
“…13,14 Enk et al reported that thermally unfolded aglycosylated CH2 region led to aggregation of Fc, and that the presence of anions destabilized the CH2 region and accelerated the aggregation reaction. 13 Kim et al reported that aggregation rates for intact antibody were strongly influenced by the conformational stability of the Fab region. 14 Furthermore, Buchner and coworkers showed that murine IgG1 domains (i.e., whole-IgG1, Fab, CH3, VH, VL, CH1, and CL) form molten-globule-like intermediate structures under specific acidic conditions (pH 2 and 100 mM NaCl; CL: pH 2, 175 mM NaCl).…”
Section: ■ Introductionmentioning
confidence: 99%